Relação entre a expressão gênica e a atividade de enzimas pectinolíticas na firmeza da polpa do mamão Golden - Broetto, Sabrina Garcia (2009)
The aim of this work was to evaluate the activity and the genic expression of the pectinmethylesterase, enzyme related to the modifications of the cellular wall, and for consequence the alterations in the quality of the fruits of the papaya tree (Carica papaya L.) cv. Golden during the whole period post-harvest, maintained in natural conditions. The fruits were picked at the development stage 2 going by sanitization and higienization. They were analyzed for 8 days after the crop (DAC) as for the modifications in the pattern of activity of the pectinmethylesterase and polygalacturonase enzymes, physical characteristics of the fruits as the firmness, besides the genic expression of the pectinmethylesterase in the fruits. The progress of the days of ripening, the firmness and the enzymatic activity were appraised as for its interrelation with the qualitative attributes of the fruits and it was observed these links directly with some characteristics. The obtained results prove the direct relationship of the activity of the pectinmethylesterase (PME) with the loss of firmness of the pulp. The activity of PME and of the polygalacturonase (PG) have synergistic action, being fundamental for the good operation of the responsible mechanisms for some of the physical changes happened in the pulp of the fruits. The analysis of the genic expression and of the activity of the pectinmethylesterase showed an antagonistic answer during the post-harvest. The increase of the expression of PME with passing of the days answered contrary to the activity of the enzyme that declined in the same period. That answer suggests the fast transcription and use of the oligonucleotides for the transformation in active proteins in the process of ripening of the fruits